PENGARUH ATURAN ETIKA TERHADAP KUALITAS AUDIT YANG DIMEDIASI OLEH PENGENDALIAN MUTU (SURVEI PADA AUDITOR BPK RI) - Korompis, Claudia Wanda Melati (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The fraud cases involving government auditors certainly erode public trust. The importance of improving audit quality to increase the public trust makes author interested in conducting research that seeks to measure the determinants of audit quality. Before Enron and Worldcom’s accounting scandal on 2001-2002, studies that measured audit quality generally still use KAP-size proxies. DeAngelo's (1981: 186), states that: "The quality of audit services is defined as a market-assessed joint venture, which will both (a) discover a breed of client's accounting system, and (b) report the breach". Ethical rules become independent variables in this study. In addition, author also added Expectancy Theory to mediate the relationship between ethical rules and audit quality represented by quality control variables. This model was inspired by Aldhizer et al. (1995) where the measure of audit quality can also be assessed from how much the level of adherence and appropriateness of the client's financial statements to the rules, laws, and applicable standards. The results of the study indicate that ethical rules have an influence on audit quality by mediating by quality control.Keywords : Ethics, Control, Audit.